2005
DOI: 10.1021/ie049263i
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Defect-Free FAU-Type Zeolite Membranes and Separation for Dry and Moist CO2/N2 Mixtures

Abstract: In this paper, the effects of synthesis conditions, including the seeding approach, gel composition, and hydrothermal treatment process, on the quality of porous R-alumina-supported Y-type FAU membranes were studied. Defect-free, pure NaY-type zeolite membranes have been synthesized and investigated for separation of equimolar CO 2 /N 2 mixtures under dry and moist conditions at atmospheric pressure. At room temperature, the CO 2 selectivity was about 31.2 for the CO 2 / N 2 dry gas mixture with a CO 2 permean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 160 publications
(124 citation statements)
references
References 37 publications
2
121
0
1
Order By: Relevance
“…For example, Dong and co-workers 68 reported that the addition of water vapor to the CO 2 /N 2 feed gas drastically reduced CO 2 and N 2 permeances and altered the membrane selectivity at low temperature (Ͻ80°C), but enhanced CO 2 selectivity at elevated temperature (140-200°C). Noble and Falconer 69 have likewise demonstrated that their SAPO-4 zeolite membranes can be used to separate CO 2 from CH 4 under a variety of pressures and temperatures, with high selectivities at 30 atm and 50°C.…”
Section: Membranes For Hydrogen Purification: An Importantmentioning
confidence: 99%
“…For example, Dong and co-workers 68 reported that the addition of water vapor to the CO 2 /N 2 feed gas drastically reduced CO 2 and N 2 permeances and altered the membrane selectivity at low temperature (Ͻ80°C), but enhanced CO 2 selectivity at elevated temperature (140-200°C). Noble and Falconer 69 have likewise demonstrated that their SAPO-4 zeolite membranes can be used to separate CO 2 from CH 4 under a variety of pressures and temperatures, with high selectivities at 30 atm and 50°C.…”
Section: Membranes For Hydrogen Purification: An Importantmentioning
confidence: 99%
“…The overall molar composition of the synthesis gel was Al 2 O 3 : 12.8SiO 2 : 17Na 2 O : 675H 2 O. 37 Once the solution was thoroughly mixed, it was heated for 12 hours at 363 K in an autoclave for hydrothermal crystallization. After the hydrothermal treatment, the powders were recovered from the autoclave and washed with DI water to a pH of ~7 by centrifuging.…”
Section: Zeolite Particle Synthesismentioning
confidence: 99%
“…The methods used for membrane synthesis are all reported in the literature. Detailed descriptions of each membrane synthesis methods are referenced: ZSM-5 membrane method was developed at Sandia 10 , Silicalite developed at NM Tech University 11 , FAU (zeolite Y) membranes used two different recipes by Kita 12 and Dong 13 , and metal doped ZSM-5 tube membranes at the University of Colorado 14 .…”
Section: On-line Testing Of Membranes (Pre and Post Modification)mentioning
confidence: 99%